Futuros y fuentes: las listas de indígenas presos en el campo de concentración de Valcheta, Río Negro (1887) - Pilar Pérez (Centre de Recherches sur les Mondes Américains, 2015)
This paper aims to be a presentation to a source that mobilizes new questions to researchers that deal with the Conquest of the Desert and the consolidation of the Argentinean state: the lists of indigenous prisoners in the concentration camp of Valcheta (1887). Firstly, we wonder about the relationship created by the “future” as a constitutive part of historical narratives. Secondly, we present our theoretical and methodological approach that we synthesize as the reconstruction of a "shattered archive". That is, a historical exercise to assemble the scattered evidence of silenced processes, particularly, due to institutional violence. Finally, the essay contextualizes the source both from its process of production as well as its circulation as part of the historical narrative that understands Valcheta as a concentration camp spatialized during the incorporation of indigenous peoples of Patagonia to the nation-state-territory matrix.